The Effect of a Childbirth Environment Model Using Complementary Therapy (Lavender Aromatherapy and Music) on Reducing Pain During the First Stage of Active Labor - Indra Yulianti (Journal of Innovative and Creativity, 2025)
Childbirth is the process of expelling the products of conception. Pain during labor is a physiological condition commonly experienced by almost all mothers giving birth. The active phase of labor occurs when the cervix opens from 4 to 10 cm, accompanied by the descent of the fetal head. This phase is usually accompanied by increased pain caused by stronger and more regular uterine contractions. Labor pain can lead to increased activity of the sympathetic nervous system, resulting in physiological changes in the body, including increased blood pressure, heart rate, and respiratory rate. If not addressed promptly, this condition will increase anxiety, tension, fear, and stress. Implementing a labor environment with complementary therapy is expected to help mothers reduce the intensity of pain during the active phase of the first stage of labor. The purpose of this study was to determine the effectiveness of implementing a labor environment with complementary therapy in reducing the intensity of pain during the active phase of the first stage of labor. The study design was a pre-experimental design with a static group comparison approach . The study population was all pregnant women who gave birth at the PMB Puri Mojokerto Health Center in January - July 2025, while the sample was 30 mothers who gave birth in August - November 2025, divided into an experimental group and a control group. The sampling technique used Purposive Sampling. The data collection technique used Verbal Descriptor Scale . Data analysis used the Wilcoxon test. The results of the study showed that most mothers in the experimental group experienced moderate pain levels in the active phase of Stage I labor, namely 80%, while in the control group more than half of the respondents experienced severe pain (60%). Comparison of labor pain levels between the experimental group and the control group, there were 3 mothers giving birth in the experimental group stating labor pain at a severe pain level than mothers giving birth in the control group, there were 7 mothers giving birth feeling the same labor pain, both in the experimental group and the control group and there were 10 mothers giving birth in the experimental group feeling labor pain in the moderate pain category than mothers giving birth in the control group. There was no difference in the intensity of labor pain between mothers giving birth who were given the application of a labor environment with complementary therapy and mothers giving birth who were not given the application of a labor environment with complementary therapy, P value = 0.052 (p> 0.05). The results of the study are expected to enable health workers to use a labor environment using complementary therapy as an alternative to reduce labor pain in the Active Phase of Stage I.